Pengaruh Teknologi Keuangan, Modal Minimum, dan Literasi Keuangan Terhadap Minat Investasi Mahasiswa di Kota Batam - Sarito, Masroni Lumban Batu; Poniman (Cattleya Darmaya Fortuna, 2025)
This study aims to examine the influence of financial technology, minimum capital, and financial literacy on students' investment interest. The background of this research stems from the low participation of students in investment activities, despite the availability of conveniences such as fintech platforms, low initial capital requirements, and access to financial information. This research uses a quantitative method with a descriptive approach and multiple linear regression analysis. Data were collected through questionnaires distributed to 95 accounting students from five universities. The results show that partially, financial technology and financial literacy have a significant influence on students' investment interest. Meanwhile, minimum capital does not significantly affect investment interest. Simultaneously, the three independent variables significantly influence students' investment interest. These findings indicate the importance of enhancing financial literacy and utilizing financial technology to encourage student participation in early-stage investment activities.